Pengaruh Brand Ambassador dan Pesan Iklan terhadap Minat Beli di Tokopedia - Hamzah, Darryl Pratama Arman; Kusnanto, Danang (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This research aims to find out, analyze and explain the phenomenon regarding the Ambassador brand and advertising messages regarding buying interest on Tokopedia on Instagram social media. This research uses quantitative methods with descriptive and verification analysis. Sampling in this study used nonprobability sampling with purposive sampling of 349 respondents, namely Tokopedia followers on Instagram social media. The data analysis tools used are path analysis techniques and scale range analysis with the help of SPSS. The research results show that the image of the Ambassador brand, advertising messages and purchase interest on Tokopedia are considered good. A fairly strong correlation exists between the Ambassador brand and advertising messages with a coefficient value of 0.405. Partially, the Brand Ambassador variable affects the purchase interest variable by 9.15% and the message advertising variable affects purchase interest by 47.87%. Meanwhile, for simultaneous testing, the Ambassador brand and message advertising significantly affected purchase interest by 57.02% and the remaining 42.98% was influenced by other variables not examined in this research.